2014
DOI: 10.3749/canmin.1400039
|View full text |Cite
|
Sign up to set email alerts
|

As-RICH APATITE FROM MT. CALVARIO: CHARACTERIZATION BY ΜICRO-RAMAN SPECTROSCOPY

Abstract: In order to investigate content and localization of arsenic in natural fluorapatite, a micro-Raman spectroscopic study was carried out on As-rich fluorapatite crystals from the volcanic region of Mt. Calvario (Mount Etna, Italy). The crystals, from both the unaltered lavas and the metasomatized rocks, show a pure fluorapatite composition in the core, but an arsenic content of up to 15 wt.% As 2 O 5 in the rim of the crystals from the altered lavas. [AsO 4 ] 3− ⇔ [PO 4 ] 3− substitutions are proposed on the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
1
1
0
2
Order By: Relevance
“…−3 can naturally occur because of its structural and electronic similarities. 35 This information justifies the similarity between the As and P fractionation profiles (Figure 2A) and their high mobility. In addition, it can be confirmed that As comes from phosphate rocks.…”
Section: Journal Of Agricultural and Food Chemistrysupporting
confidence: 77%
See 1 more Smart Citation
“…−3 can naturally occur because of its structural and electronic similarities. 35 This information justifies the similarity between the As and P fractionation profiles (Figure 2A) and their high mobility. In addition, it can be confirmed that As comes from phosphate rocks.…”
Section: Journal Of Agricultural and Food Chemistrysupporting
confidence: 77%
“…Apatite, mainly fluorapatite (Ca 5 (PO 4 ) 3 F), is the predominant mineral in phosphate rocks, which are used in the production of phosphate fertilizers. These minerals are treated with H 2 SO 4 to increase the solubility of phosphate, a primary nutrient. , In these minerals, the substitution of PO 4 –3 for AsO 4 –3 can naturally occur because of its structural and electronic similarities . This information justifies the similarity between the As and P fractionation profiles (Figure A) and their high mobility.…”
Section: Resultsmentioning
confidence: 96%
“…Апатит кристаллизуется в широком интервале физико-химических условий, однако его состав часто позволяет интерпретировать эти условия [1,2]. Мышьяковистый апатит, судя по доступной опубликованной литературе, является очень редким [3] и условия его формирования изучены слабо. В изученных породах стабильные концентрации Cl в As-апатите являются свидетельством образования в гипогенных условиях, а не гипергенных.…”
unclassified
“…Na produção de fertilizante, esses minerais são tratados com H2SO4 para aumentar a solubilidade do fosfato, um nutriente primário (Perez-Lopez et al, 2007;Pérez-López et al, 2010). Nesses minerais pode ocorrer, naturalmente, a substituição de PO4 -3 por AsO4 -3 , devido às suas similaridades estruturais e eletrônicas (Gianfagna et al, 2014). Figura 13.…”
Section: Fracionamento Pelo Protocolo De Extrações Sequenciais -Bcr (unclassified